Effects of Bloodletting and Cold Stress Treatment before Slaughter on Flavor Quality of Fresh Silver Carp Fillets - NIU Yongxin, XIONG Qing, HU Yang, LIU Ru, YIN Tao, YOU Juan, AN Yueqi, XIONG Shanbai (Shipin Kexue, 2025)
To determine the appropriate pre-slaughter treatment, the effects of four different pre-slaughter treatments: stunning (CK), tail artery bloodletting (TS), neck artery bloodletting (NS), and cold stress (CS) on the flavor quality of silver carp fillets were studied using gas chromatography-mass spectrometry (GC-MS), ultra-high performance liquid chromatography (UPLC), a taste analyzer, and an odor analyzer. The results indicated that the pre-slaughter treatments had a significant effect on the taste and odor qualities of silver carp fillets, which were significantly improved by both bloodletting and cold stress treatments. Compared with the CK group, the contents of bitter amino acids, adenosine monophosphate, and guanosine monophosphate in the TS, NS and CS groups significantly decreased (P < 0.05), while the content of hypoxanthine nucleoside significantly increased (P < 0.05). The content of adenosine diphosphate in the TS and CS groups, the betaine content in the TS and NS groups, and the carnosine content in the CS group decreased markedly. Bloodletting and cold stress treatments raised the proportion of umami and sweet amino acids in silver carp fillets while decreasing the contents of bitter and sour amino acids, thereby resulting in enhanced umami and sweet taste. The relative contents of heptanal, (E)-2-heptenal, nonanal, decanal, (E,E)-2,4-decadienal, and 2,3-octanedione, contributing to fishy, oily, and overcooked flavors, significantly decreased in the TS, NS, and CS groups, while the relative contents of (E,E)-2,4-heptadienal and 2,3-pentanedione, contributing to nutty and buttery flavors, significantly increased. In conclusion, bloodletting and cold stress treatments before slaughter could significantly reduce the earthy smell of fresh silver carp fillets, thus improving its odor quality.